Evaluation of an improved Streptex kit for the grouping of beta-haemolytic streptococci by agglutination. Issue 7 (July 1982) - Castle, D; Kessock-Philip, S; Easmon, C S
Abstract : A modified Streptex kit in which the extraction procedure had been simplified was used to group 200 streptococcal strains. Positive reactions could be obtained with live colonies and over 90% of isolates were correctly grouped from primary isolation plates. Some minor cross-reactions were seen with Streptex, but these were not strong enough to cause any confusion and no isolates were incorrectly grouped. The extraction enzyme in the Streptex kit was relatively poor at extracting the group-specific teichoic acid of group D strains but worked well with groups A, B, C, F and G.